Pre-reinforcement Performance of Yielding Anti-slide Piles for Bedding Rock Slope - DING Wei; WANG Junjie; QIU Zhenfeng (Renmin Zhujiang)
Yielding anti-slide pile is a pre-reinforcement structure developed for bedding rock slopes.To explore its pre-reinforcement performance,firstly,its pre-reinforcement mechanism is analyzed.Secondly,by employing deformation and stress as reference indicators,this paper adopts a physical model test combined with numerical simulations to compare yielding anti-slide piles with ordinary anti-slide piles.Finally,the effects of yielding layer thickness,anchoring section length,and yielding layer elastic modulus on the reinforcement effect of yielding anti-slide piles are studied.The results are as follows.① The pre-reinforcement and yielding anti-slide piles for slopes can induce weak deformation of potential sliding mass through the yielding layer setting,exert the beneficial effect of shear strength between layers of rock strata,and improve the displacement and stress state of the pile bodies.② The displacement of rock stratum sliding during the support of yielding anti-slide piles is significantly increased,and the lateral pressure acting on the pile bodies is smaller than that of ordinary anti-slide piles to better improve the anti-slide effect of anti-slide piles.③ The pre-reinforcement effect of the yielding anti-slide piles tends to gradually improve with the rising length of the anchor section,while the yielding layer thickness and the elastic modulus of the yielding layer increase with a trend of first becoming better and then becoming worse.